Decisions of intelligent support for supplier selection - Juozas Bivainis; Jonas Dieninis; Daina Jansevičiūtė (Business: Theory and Practice, 2012)
This paper examines the problem of supplier selection. The supplier selection process has been expressed as decision cycle, which involves such phases: searching for suppliers, preliminary selection, complex evaluation, negotiations, preparing a contract, monitoring. The present situation in this field has been described in such a way: large interest to increase validity of decisions for supplier selection from side of business practice, diversity of methods and models for supplier selection suggested by researchers, the episodic character of putting into practice this methodical potential. In order to improve such a situation, we see a need to develop the medium of intelligent support for supplier selection decisions. The suggested variant of integrated decisions intelligent support system is provided. The components of expert judgment support, individual decision support, group decision support and negotiations support have been incorporated into proposed system. The content and process of decisions support have been specified in accordance with character of every phase of supplier selection cycle.